Micro-Credit Services and Growth of Women Enterprises in Rwanda: A Case of Urwego Opportunity Bank - Mukamuhoza, Providence; Kengere, Osiemo Athanas; Nyabera, Onsoti Sammy (Journal of Finance and Accounting, 2023)
This study delved into the pivotal role played by micro-credit services in advancing the growth of enterprises led by women in Rwanda, with a dual focus on their impact on both business development and enhancements in family lifestyles. Employing a descriptive survey research approach that integrated quantitative and qualitative methods, the research aimed to offer a comprehensive understanding of the subject. The primary objective revolved around examining the influence of micro-credit services on the growth of women-led enterprises, with specific objectives geared towards evaluating the effects of both financial and non-financial services on this growth trajectory. The target population encompassed 350 individuals, including women beneficiaries and employees affiliated with UOB in the Gasabo District. Using Slovene’s formula, the sample size was determined at 186 respondents, with a confidence interval of 95% and a margin of error of 5%. Participant selection involved simple random sampling, employing a structured questionnaire as the primary data collection instrument. Key findings underscored the positive impact of small credit from UOB on the business activities of 69.6% of respondents. In terms of the influence of micro-credit services on family lifestyles, 58.7% strongly agreed, and 23.9% agreed that a significant improvement had been witnessed. Furthermore, 67.4% of participants acknowledged the contributory role of the accessibility of micro-credit services in poverty eradication. Statistical analysis using SPSS revealed a substantial and positive relationship (0.914*) between micro-credit services and the growth of women-led enterprises, underscoring the significance of these services in fostering the overall development of businesses led by women. In conclusion, the research highlighted the notable role of micro-credit services in propelling the growth of enterprises led by women in Rwanda. The positive relationship established through statistical analysis emphasizes the potential impact of such financial interventions in empowering women entrepreneurs and contributing significantly to poverty alleviation in the region. A researcher recommended that it is good for the government and enterprises undertakers continuing to support this opportunity by offering and improving the services towards women enterprises through micro credit services. Keywords: Micro-Credit Services, Growth of Women Enterprises, Urwego Opportunity Bank, Rwanda